1973
DOI: 10.1111/j.1365-2672.1973.tb04140.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Progression in Sliced Vacuum Packaged Bacon at Refrigeration Temperatures

Abstract: Three hundred and forty eight strains of micro-organisms were isolated from packaged bacon which had been cured by one or other of 2 methods (A and B) and stored at &loo for 7 weeks. Before storage, Micrococcus sub-group 7 (47%) and corynefonn bacteria (33%) were the principal contaminants of bacon cured by method A and Micrococcus subgroup 1 (20%) and Microbacterium thermosphactum (21%), in bacon cured by method B. After 7 days at O", coagulase negative staphyIooocci accounted for 10 and 33% of the microflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Our results confirm previous findings that lactic acid bacteria and micrococci are the commonest bacteria on vacuum-packed bacon after storage below 25OC (Eddy & Gatherum 1961;Tonge et al 1964;Dempster 1973). There were, however, considerable differences in both the numbers and types of organisms on the fat and lean portions of the same bacon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm previous findings that lactic acid bacteria and micrococci are the commonest bacteria on vacuum-packed bacon after storage below 25OC (Eddy & Gatherum 1961;Tonge et al 1964;Dempster 1973). There were, however, considerable differences in both the numbers and types of organisms on the fat and lean portions of the same bacon.…”
Section: Discussionsupporting
confidence: 92%
“…Tonge et al (1964) found that group D streptococci was the commonest type in their low-salt bacon after storage at 20° and 30 OC. Dempster (1973) studied two bacon samples during storage at 1 OC. Aciduric lactobacilli grew on bacon produced by a 'hygienic process', whereas group N streptotocci, non-aciduric lactobacilli and, to a lesser extent, group D streptococci were detected on a smoked 'sweet-cured bacon'.…”
Section: Discussionmentioning
confidence: 99%